The Eigenvalues of a Class of Elliptic Differential Operators (Journal of Partial Differential Equations, 2023)
Consider $\left(M,g\right)$ as an $n$-dimensional compact Riemannian manifold. In this paper we are going to study a class of elliptic differential operators which appears naturally in the study of hypersurfaces with constant mean curvature and also the study of variation theory for $1$-area functional.
Keywords: Eigenvalue problem; elliptic operators; Bochner type formula.